The joy of gratifications: Promotion as a short-term boost or long-term success – The same for women and men? - Siegmar Otto; Vincent Dekker; Hannah Dekker; David Richter; Sarah Zabel (Human Resource Management Journal, 2021)
Job satisfaction helps create a committed workforce with many positive effects, such as increased organisational citizenship behaviour and reduced absenteeism. In turn, job satisfaction can be increased through gratifications, such as wage increases and promotions. But human satisfaction is prone to being governed by the homeostatic principle and will eventually return to the individual's base level. Thus, we longitudinally examined the effects of promotions to managerial positions and pay raises on job satisfaction across a period of 27~years. Our analyses were based on a large-scale representative German panel (N~=~5978 observations) that allowed us to separate the effect of a promotion from the effect of the corresponding wage increase. We found that promotions positively affected job satisfaction in the short term but diminished after 1~year. Furthermore, the influence of a promotion on job satisfaction was more pronounced for men than for women.
Keywords: 650; gender; job satisfaction; promotion; reward; wages